Phenotypic and molecular analysis of staphylococcus aureus for carriage and transmission in a student population in a Malaysian public university - Mat Azis, Norhidayah (2015)
Staphylococcus aureus is a human commensal bacteria that colonize the skin and mucosal surfaces of healthy individuals. This opportunistic pathogen is the most common nosocomial pathogen responsible for life-threatening diseases in humans worldwide. The anterior nares are the most frequent colonization site for S. aureus and nasal carriage is a major risk factor for infections and a source of transmission of this pathogen. The incidence of S. aureus and MRSA are growing at an alarming rate not only in the healthcare settings but also in the community. In this regards, this study aims to assess the S. aureus carrier rate and persistence, risk factors for nasal carriage, antimicrobial resistance and epidemiological molecular characteristics among the university student population. A set of self-administered questionnaires on socio-demographics, hygienic practices, medical and medication history together with a consent form were distributed prior to nasal swab collection. The collection was done twice in a one month interval during October and November 2013 from 192 and 180 health sciences students, respectively, at the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. Identification of bacteria isolated was done based on basic phenotypic methods. All S. aureus isolates were subjected to antibiotic susceptibility test (AST) by Kirby-Bauer disc diffusion method against eight antibiotics and screened for MRSA by PCR detecting the mecA gene. All mecA positive isolates were subjected to staphylococcal cassette chromosome (SCC) mec typing, multilocus sequence typing (MLST) and eBURST analysis. All isolates were further characterized by spa typing, screening of PVL genes and enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR). In this study, the colonization rates of S. aureus was 31.3% (60/192) and 33.3% (60/180) of the student population during the first and second sampling respectively. Thirty-nine (65%) students were detected for S. aureus at both isolation events and referred as persistent carriers. There is no significant correlation between the carriage and the tested risk factors except for the habit of touching the nose and chronic illnesses (P<0.05). All 120 S. aureus isolates from both isolation events were susceptible towards vancomycin, ciprofloxacin and gentamycin. The highest frequency of resistance was observed for penicillin at both isolations (70% and 65% respectively). This was followed by tetracycline with a similar resistance rate (11.67%) in both isolation events. Low level of resistance was observed against erythromycin at both events. This indicates the persistence of the antimicrobial resistance pattern in the population over the short study period. As for methicillin resistance, out of the 120 isolates of S. aureus, 10 (8.33%) were positive for the mecA gene with four and six isolates from first and second isolation events respectively; four isolates were from two individuals. However, among the mecA positive isolates, only eight isolates showed resistance towards cefoxitin (four isolates from each isolation event) while the other two mecA positive isolates (from second event) were cefoxitin-susceptible by both dics and Etest methods. The mecA-positive isolates belonged to SCCmec types I (n=9) and V (n=1). MLST analysis of MRSA isolates revealed three STs: ST508 (n=1), ST88 (n=1) and ST96 (n=1) while other seven of MRSA isolates showed non typeable sequences type. This indicates the tendency of MRSA to persist, although at a low rate with limited genotypes. eBURST analysis showed that MRSA isolates found in this study were potentially related to those MRSA found in Asian countries and might be disseminated regionally. Based on ERIC analysis, the majority of isolates were largely genetically distinct. As for the persistent S. aureus carriers, it was found that for 19 (48.72%) of them, respective individual carried S. aureus of a similar spa type during both isolation events. This indicates the persistence of certain spa types in the respective individuals over the short term period. Although the prevalence of S. aureus carriage and MRSA in this study cannot be generalized to entire population due to limitations of the study, but this indicates the need of periodic screening to monitor S. aureus and MRSA status among community.